1990
DOI: 10.1016/0735-1097(90)92813-h
|View full text |Cite
|
Sign up to set email alerts
|

Early ambulation after 5 French diagnostic cardiac catheterization: Results of a multicenter trial

Abstract: Because earlier ambulation and discharge after cardiac catheterization may result in the increased utilization of outpatient facilities, a prospective five center clinical pilot trial assessing the safety and outcome of early ambulation after routine left heart catheterization was performed in 287 patients. Catheterization routines at each clinical center were unchanged throughout the study. After the diagnostic catheterization using 5 French (F), preformed, large lumen catheters and arterial puncture compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
4

Year Published

1996
1996
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(46 citation statements)
references
References 18 publications
4
38
0
4
Order By: Relevance
“…Wood et al [1] point out that the rate of hematoma formation in their study was significantly lower than previously reported in similar studies [2][3][4]. They also point out that with the lower-thanexpected complication rate, the clinical relevance of such a study would be questionable.…”
mentioning
confidence: 77%
“…Wood et al [1] point out that the rate of hematoma formation in their study was significantly lower than previously reported in similar studies [2][3][4]. They also point out that with the lower-thanexpected complication rate, the clinical relevance of such a study would be questionable.…”
mentioning
confidence: 77%
“…Contudo, mais recentemente, têm-se observado igualmente bons resultados com cateteres menores ainda 4 , percebendo-se uma tendên-cia ao emprego destes instrumentais de menor calibre para que, ainda com a manutenção da qualidade das imagens, reduzirem-se mais as complicações vasculares e agilizar-se a alta hospitalar [4][5][6][7] . São, no entanto, muito escassas as informações a respeito de cateteres de muito pequeno diâmetro (<5F).…”
Section: Objetivo -Avaliar a Eficiência A Segurança E A Praticidade unclassified
“…Uma hora após, conseguiu-se, na maioria dos pacientes (85%), uma deambulação segura e sem complicações hemorrágicas, na via de acesso. Kern e col 4 , com o uso de cateteres 5F, necessitaram quase três vezes este tempo, Brown e col 5 , sete vezes e Carosio e col 7 , oito vezes. A minimização do tempo de imobilização é um fato de grande importância, não só na percepção do paciente quanto à traumaticidade e invasividade do exame, quanto na agilização da ocupação e alta do leito hospitalar, com importante impacto na sua reutilização, no mesmo dia e, evidentemente, nos custos de saúde.…”
Section: Tabela I -Estudos Utilizando Cateteres De Baixo Perfilunclassified
See 1 more Smart Citation
“…Not only does this requirement increase the time and discomfort involved for the patient, but it also tends to increase costs associated with the procedure by making its performance on an outpatient basis difficult. While there are currently efforts being made to increase the number of outpatient procedures using the conventional compression method [9,10], a new method of achieving safe and rapid hemostasis with reduced complications would allow earlier mobilization. More rapid mobilization might permit more outpatient procedures which have been found to cut costs [11][12][13] as well as ease patient anxiety and discomfort [14,15].…”
Section: Introductionmentioning
confidence: 99%